Acute Renal Graft-Versus-Host Disease in a Murine Model of Allogeneic Bone Marrow Transplantation. Issue 8 (August 2017) - Schmid, Peter M.; Bouazzaoui, Abdellatif; Schmid, Karin; Birner, Christoph; Schach, Christian; Maier, Lars S.; Holler, Ernst; Endemann, Dierk H.
Acute kidney injury (AKI) is a very common complication after allogeneic bone marrow transplantation (BMT) and is associated with a poor prognosis. Generally, the kidneys are assumed to not be no direct targets of graft-versus-host disease (GvHD), and renal impairment is often attributed to several other factors occurring in the early phase after BMT. Our study aimed to prove the existence of renal GvHD in a fully major histocompatibility complex (MHC)-mismatched model of BALB/c mice conditioned and transplanted according to 2 different intensity protocols. Syngeneically transplanted and untreated animals served as controls. Four weeks after transplantation, allogeneic animals developed acute GvHD that was more pronounced in the high-intensity protocol (HIP) group than in the low-intensity protocol (LIP) group. Urea and creatinine as classic serum markers of renal function could not verify renal impairment 4 weeks after BMT. Creatinine levels were even reduced as a result of catabolic metabolism and loss of muscle mass due to acute GvHD. Proteinuria, albuminuria, and urinary N -acetyl-beta-d -glucosaminidase (NAG) levels were measured as additional renal markers before and after transplantation. Albuminuria and NAG were only significantly increased after allogeneic transplantation, correlating with disease severity between HIP and LIP animals. Histological investigations of the kidneys showed renal infiltration of T cells and macrophages with endarteriitis, interstitial nephritis, tubulitis, and glomerulitis. T cells consisted of CD4+, CD8+, and FoxP3+ cells. Renal expression analysis of allogeneic animals showed increases in indoleamine-2, 3 dioxygenase (IDO), different cytokines (tumor necrosis factor α, interferon-γ, interleukin 1 α [IL-1α], IL-2, IL-6, and IL-10), and adhesion molecules (intercellular adhesion molecule 1 and vascular cell adhesion molecule 1), resembling findings from other tissues in acute GvHD. In summary, our study supports the entity of renal GvHD with histological features suggestive of cell-mediated renal injury. Albuminuria and urinary NAG levels may serve as early markers of renal impairment.